2004
DOI: 10.1038/sj.bjc.6602177
|View full text |Cite
|
Sign up to set email alerts
|

Epirubicin carboplatin and 5-fluorouracil (ECarboF) chemotherapy in metastatic hormone refractory prostate cancer

Abstract: The aim of this study was to examine the efficacy and toxicity of the epirubicin, carboplatin and 5-fluorouracil (ECarboF) regime in patients aged 70 or less with metastatic prostate cancer resistant to LHRH analogues. The majority of patients had previously received steroids as part of their systemic management and had progressive disease on steroids. In total, 80 patients were treated over a 6-year period, with objective response rates (PSA or radiological) of 45% and median time to relapse of 9.5 months. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Platinum containing regimens such as epirubicin, carboplatin and 5-flurouracil have also shown antitumour activity in phase II studies (Birtle et al, 2004) and their activity in patients who fail docetaxel treatment is undergoing evaluation. Satraplatin (JM-216), an oral platinum compound, is currently being evaluated in a large international trial (SPARC), in combination with prednisolone as second-line treatment after docetaxel.…”
Section: Current Treatmentsmentioning
confidence: 99%
“…Platinum containing regimens such as epirubicin, carboplatin and 5-flurouracil have also shown antitumour activity in phase II studies (Birtle et al, 2004) and their activity in patients who fail docetaxel treatment is undergoing evaluation. Satraplatin (JM-216), an oral platinum compound, is currently being evaluated in a large international trial (SPARC), in combination with prednisolone as second-line treatment after docetaxel.…”
Section: Current Treatmentsmentioning
confidence: 99%
“…Chao and colleagues 7 initially reported the use of ECF in 21 patients with metastatic CRPC, and reported a response rate of 43% including objective response in 3 of 5 patients with liver metastases. Birtle and colleagues 9 reported on 80 patients with CRPC treated with ECarbF, and although no patients had visceral metastases, objective response was observed in 6 of 7 patients. Combining these data with our report provides an objective response rate of 62% (95% CI, 32-85%) for patients with liver metas- gupta et al 14 reported on the use of ECarb plus IV bolus 5-fluorouracil in CRPC patients treated following prior progression despite docetaxel.…”
Section: Discussionmentioning
confidence: 99%
“…8 curve) 5 was substituted for cisplatin given that carboplatin has also been active in combination with epirubicin and 5-fluorouracil. 9 All patients received prednisone 5 mg by mouth twice a day, and continued on ADT. Complete clinical and toxicity reviews were conducted at the beginning of each cycle.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that "The number of dose reductions and treatment delays illustrate that this is an aggressive regime. It would, therefore, not be suitable for the majority of patients, but should be considered for the sizeable minority in whom combination chemotherapy is appropriate [18]." Doxil, the newest anthracycline, has been tried as a single agent in the treatment of metastatic prostate cancer.…”
Section: Mitoxantronementioning
confidence: 99%
“…Birtle recently examined the combination of epirubicin, carboplatin, and 5-fluorouracil in metastatic, hormone refractory, prostate cancer [18]. 93% of patients (75/80) were evaluable for toxicity.…”
Section: Mitoxantronementioning
confidence: 99%